Ensuring and Monitoring the Needs and Facilities for Preschool Children’s Development - Mohammad Taghipour; Neda Ghiasvand (International Journal of Children, 2024)
When all of a city's residents' requirements are met, it might be considered desirable. As a segment of the population, children ought to be given as much consideration as feasible while designing metropolitan areas. The current study sought to understand the relationship between addressing preschoolers' basic requirements and providing the facilities they require, as well as keeping track of how well those needs are being met at each developmental stage. Children's drawings and questionnaires serve as the primary data collection instruments in this descriptive-analytical study design. In this study, 25 parents and 25 children between the ages of 5 and 7 make up the sample size. The statistical analysis program utilized was Amos together with Spss. There were four primary themes identified from the child interviews and drawings. The teaching of life skills was the first major focus; social damage prevention was the second; artistic and creative skills were the third; sports and game-based skills constituted the fourth and final primary themes. The findings of the research show that in creating a child-friendly city, all components, needs and factors in its creation should be evaluated and measured, in which children can, as a researcher, play the role of leading the evaluation and measurement process. This role is not only related to the design of research related to the creation of a child-friendly city, but also includes the collection and analysis of data and information. Adults should facilitate children's participation in this field through necessary support, training and capacity building. Children can express opinions very different from those of adults and strengthen the responsiveness of those active in child-friendly cities.
Keywords: Artistic and Creative Skills; Child-Friendly City; Children’s Participation; Developmental Stages; Life Skills Education